(untitled) (Brazilian Geographical Journal, 2012)
Nowadays, understanding of climate change effect in the reduction of the ice cover is a relevant issue. Resolving this question is a challenge because ice bodies can respond in different ways to climate change. The reduction of the ice cap region is strong in Patagonia. Consequently, this paper is focused on the review of data in order to document glacier alterations in the Chilean Patagonian during the 20th century and beginning of the 21th century. There are some authors who have documented the influence of climate change in Patagonian ice fields (Masiokas et al., 2009; Veblen et al., 2011). Much data shows a generalized thinning and retreat trend of glaciers in the Northern Patagonia Icefield (NPI) and the Southern Patagonia Icefield (SPI). Furthermore, the contribution that Patagonian glacier retreat makes to sea level rise (SLR) is one of the important issues of the interaction between glaciers and climate change. An original analysis of glaciers HPN2 and HPN3 conducted for this paper provides additional support for the general recession of glaciers Patagonia.